The Regulation of Digital Trade : Key Policies and International Trends - Daza Jaller, Lillyana; Gaillard, Simon; Molinuevo, Martín (World Bank, Washington, DC, 2020)
One day, people will wonder how global trade was even possible with before goods and services were bought and sold in global digital markets without regard or even knowledge of where sellers and buyers where located. We are not there yet --not by a long shot. For now, digital trade remains segmented mostly along national and regional boundaries, due largely to a combination of lack of consumer trust in online transactions and regulatory differences across borders, as well as the inherent challenges of moving goods internationally. Regulation plays a central role in building the foundations of digital markets. It can provide the legal tools necessary for remote contracts, clarify the rights and obligations of the multiple actors involved in digital transactions, and establish a framework that promotes consumer trust in digital markets, even when the consumer does not know the merchant or when the merchant is in a different country. However, regulation can also further segment digital trade, de facto restricting digital transactions to within national boundaries, or allowing for cross-border transactions with some partners to flourish, while limiting others. This can be the intended result of regulatory measures that limit cross-border data flows or online purchases or may be the undesired effect of regulatory differences across countries that leads businesses to offer different goods and services across boundaries.